STABILITY OF STRUCTURES OF BUILDINGS AND STRUCTURES FROM PARASEISMIC EFFECTS (DETONATION WAVES) (Spectrum Journal of Innovation, Reforms and Development, 2022)
A brief review of paraseismic forces that affect the structures of buildings and structures is presented. We also refer to paraseismic forces the energy of a detonation wave, which is capable of influencing the structures of buildings and structures. The influence of a detonation wave on the structures of buildings and structures has been studied for many years using the developed gas detonation unit, which makes it possible to cause artificial ground vibrations. The basics of the technique and the scheme of the experiments are presented. The principle of operation of a gas detonation unit that causes a detonation wave is described, and schemes of the impact of these waves on the structures of selected buildings are given. A method for controlling the frequency and strength of the induced vibrations by choosing the composition and amount of the combustible mixture for the gas detonation unit is highlighted.